Issues on Water Privatization Under New Regulation: Evidence in Indonesia - Hermawan, Sapto; Hananto, Supid Arso (Comparative Law Review, 2022)
Water plays a vital role in every human life, so the availability and sustainability of water resources need to be carefully regulated. This article attempts to analyse water governance in Indonesia under the new water resources regulation, mainly the issue of water privatization. This article is classified as normative legal research. This article shows that even though the State gives the water privatization licence to the private sector as the last priority, it seems that the Indonesian people will still encounter the same problem in the coming year. This article argues that the issue of distribution of water justice, water access, and violations of the water right related to water utilization on a large scale are challenges for the Indonesian government to resolve.